Asterosap, an Egg Jelly Peptide, Elevate Intracellular Ca2+ and Activate the Motility of Spermatozoa - Islam, MS; Akhter, T; Matsumoto, M (Progressive Agriculture, 2013)
Components from the outer envelopes of the egg that influence the flagellar beating and acrosome reaction of spermatozoa are regulated by ion flux across the plasma membrane. Asterosap, a sperm-activating peptide from the starfish egg jelly layer, causes a transient increase in intracellular cyclic GMP (cGMP) through the activation of the asterosap receptor, a guanylyl cyclase (GC), and causes an increase in intracellular Ca2+. Here we describe the pathway of asterosap-induced Ca2+ elevation using different Ca2+ channel antagonists. Fluo-4 AM, a cell permeable Ca2+ sensitive dye was used to determine the channel caused by the asterosap-induced Ca2+ elevation in spermatozoa. Different L-type Ca2+ channel antagonists, a non specific Ca2+ channel antagonist (nickel chloride), and a store-operated Ca2+ channel (SOC) antagonist do not show any significant response on asterosap-induced Ca2+ elevation, whereas KB-R7943, a selective inhibitor against Na+/Ca2+ exchanger (NCX) inhibited effectively. We also analyzed the flagellar movement of spermatozoa in artificial seawater (ASW) containing the asterosap at 100 nM ml?1. We found that spermatozoa swam vigorously with more symmetrical flagellar movement in asterosap than in ASW and KB-R7943 significantly inhibited the flagellar movement. DOI: http://dx.doi.org/10.3329/pa.v19i1.17358 Progress. Agric. 19(1): 79 - 88, 2008